2017
DOI: 10.1515/helm-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and inactivation of proteolytic enzymes by Triaenophorus nodulosus (Cestoda)

Abstract: SummaryThe proteolytic activity in washings off the Triaenophorus nodulosus cestode tegument and the ability of the worms to inactivate proteolytic enzymes were studied. It was found that the major proteolytic activity in the washing samples is represented by the easily desorbed fraction most probably characterizing the activity of the host's enzymes. Serine proteinases are an essential part of these enzymes. It was shown that the worms' incubation medium and their homogenates can inhibit host proteinases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
(26 reference statements)
2
10
0
Order By: Relevance
“…While extensive pathologies have been reported within the livers of fish harbouring this parasite (Kuperman, 1981; Hoffman et al , 1986; Brinker & Hamers, 2007), no morphological effect on the intestine has been documented, although it is not known if these studies paid any particular attention to this organ. Only changes to the activity of intestinal enzymes in these infected fish have been reported so far (Izvekova & Izvekov, 2013). Therefore pathological changes to the intestine of perch as a result of T. nodulosus E/S products are likely and in vitro studies on other fish cestodes indicate that these products will provoke host cellular immune responses (Morley & Hoole, 1997; Scharsack et al , 2013).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…While extensive pathologies have been reported within the livers of fish harbouring this parasite (Kuperman, 1981; Hoffman et al , 1986; Brinker & Hamers, 2007), no morphological effect on the intestine has been documented, although it is not known if these studies paid any particular attention to this organ. Only changes to the activity of intestinal enzymes in these infected fish have been reported so far (Izvekova & Izvekov, 2013). Therefore pathological changes to the intestine of perch as a result of T. nodulosus E/S products are likely and in vitro studies on other fish cestodes indicate that these products will provoke host cellular immune responses (Morley & Hoole, 1997; Scharsack et al , 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore pathological changes to the intestine of perch as a result of T. nodulosus E/S products are likely and in vitro studies on other fish cestodes indicate that these products will provoke host cellular immune responses (Morley & Hoole, 1997; Scharsack et al , 2013). When combined with known T. nodulosus effects on the activity of host digestive enzymes (Izvekova & Izvekov, 2013), a profound alteration in the suitability of the fish intestine as an environment for the establishment and growth of other helminths is to be expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we found no significant inhibitory effect of E. rugosum incubation medium on trypsin activity (Izvekova et al, 2017a). However, since the incubation medium of another cestode, Triaenophorus nodulosus, living in the pike intestine was found to inhibit trypsin samples (Izvekova et al, 2017b), we have changed the experimental design to search for a similar capacity in E. rugosum. Thus, in the previous experiment, the worms were incubated in 5 ml of Ringer's solution, and now, the solution volume was reduced to 2.5 ml to minimize dilution and enhance a possible inhibitory effect.…”
Section: Discussionmentioning
confidence: 95%